2018
DOI: 10.33546/bnj.360
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hypnobirthing on the Progress of the Latent Phase of Labor in Primigravida

Abstract: Background: The first stage of labor is a tiring moment for mothers, which may cause exhaustion, dehydration, risk of infection, uterine atony, and postpartum hemorrhage. Hypnobirthing is considered effective to speed up early labor process. Objective: This study aimed to examine the effect of hypnobirthing on the progress of the latent phase of labor.Methods: This study was a quasi experiment with posttest only control group design. Thirty-two primigravida mothers in the latent phase of labor were selected us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
(3 reference statements)
1
4
0
Order By: Relevance
“…The result of the current study is in congruent with that of Abdel Azeem & Mohamady (2019) who found that the mean descent of the presenting part was evident among the supportive care group than the control group during the active stage of labor, with statistically significant differences (P < 0.001). More over the result of present study is in line with that of (Muhidayati et al, 2018) who reported a statistically significant difference between breathing exercise and control groups regarding the progress of the fetal head descent.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The result of the current study is in congruent with that of Abdel Azeem & Mohamady (2019) who found that the mean descent of the presenting part was evident among the supportive care group than the control group during the active stage of labor, with statistically significant differences (P < 0.001). More over the result of present study is in line with that of (Muhidayati et al, 2018) who reported a statistically significant difference between breathing exercise and control groups regarding the progress of the fetal head descent.…”
Section: Discussionsupporting
confidence: 92%
“…Also (Muhidayati et al, 2018) supported the same idea and reported that a significant effect of breathing exercises on frequency and duration of uterine contraction, So the use of this methods can be suggested as a supplement nonpharmacological method alternative for augmenting uterine contractions instead of oxytocin because, it does not have the side effects of oxytocin.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The increase in adrenaline has an impact on the contraction of blood vessels so that there is a decrease in oxygen supply to the fetus, so that uterine contractions weaken and result in the length of the labor process (Safitri et al, 2019). Several studies have shown that the level of maternal anxiety affects the length of the first stage of labor (Setiani et al, 2020); (Safitri et al, 2019); (Widiawati, 2019); (Difarissa et al, 2016); (Masruroh, 2015); (Muhidayati et al, 2018).…”
Section: The Effect Of Maternal Anxiety Levels On the First Stage Of ...mentioning
confidence: 99%
“…Anxiety and fear of mothers during childbirth can have an impact on the onset of severe pain and can also result in decreased uterine contractions, so that childbirth takes longer (Setiani et al, 2020). A study on hypnobirthing shows that hypnobirthing has an effect on increasing the frequency of uterine contractions, the duration of contractions, the opening of the cervix, and the decrease in the head of the fetus, so that it will speed up the delivery process (Muhidayati et al, 2018). The effect of hypnobirthing on the duration of delivery during II is proven by the research of Syswianti et al (2020) and (Rini, 2010).…”
Section: Introductionmentioning
confidence: 98%